MAJOR OVERHAUL PIPELINES USING COMPOSITE MATERIALS - Мартинюк, Ростислав Тарасович; Мартинюк, Ольга Ростиславівна; Джунусов, Віталій Аматаєвич (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The purpose of this article is to describe the method of repair pipelines using composite materials, compare, identify the advantages or disadvantages of a particular method, and the conditions under which it is possible or necessary to its use.